E-Marketing Skills Required by Start-up Operators for Effective Management of Small and Medium Scale Enterprises - N. Egbu, Virginia; Azih, Nonye (British Journal of Marketing Studies, 2023)
The study ascertained the “E-Marketing Skills Required by Start-up Operators for Effective Management of Small and Medium Scale Enterprises” in Ebonyi State. One research question guided the study with one null hypothesis tested at 0.05 level of significance.  A sample of 261 was selected from the population of 745 Start-up operators of small and medium scale enterprises using Yaro Yamane formula. Data was collected using 15 items structured questionnaire of four points scale. The instrument was validated by three experts from Ebonyi State University. The reliability index of the instrument was 0.80. Data collected from the research question was analyzed using mean and standard deviation while t-test statistics tested the hypothesis at 0.05 level of significance. Findings from this study revealed that e-marketing skills are highly required by start-up operators for effective management of small and medium scale enterprises in Ebonyi State and that gender influenced the views of the respondents. Based on the findings of the study it was concluded that e-marketing skills are highly required for effective management of small and medium scale enterprises to achieve a sustainable competitive advantage over other fierce rivalries in the market space. It is therefore recommended among others that training of SMEs managers on e-marketing skills for adequate utilization of the skills in business management be treated as critical strategy to close the gap between traditional marketing and digital marketing system.